State-mandated decentralized irrigation reforms: (re)thinking Africa’s irrigation commons using the state-reinforced self-governance framework - Emmanuel Frimpong Boamah; Thomas Yeboah; Kahad Adamu; Fuzhen Yin; Enoch Yeleliere; Thomas Padi Appai; Kwaku O Twum (Ecology and Society)
The prospects and challenges of decentralized irrigation governance reforms are widely discussed. Less discussed, however, is the institutional design of these reforms and how and why it matters to our diagnosis of their successes or otherwise. We used and tested the state-reinforced self-governance (SRSG) framework to examine the institutional design of Ghana’s decentralized irrigation reform and whether self-governance capacities were granted to irrigators or water users associations (WUAs). We focused on the Kpong Irrigation Scheme (KIS) as our case study, surveying and interviewing water users/farmers, leaders of WUAs, and other stakeholders with knowledge and experience about the decentralized irrigation reform. We also analyzed the contents of key policy/regulatory documents for managing the decentralized irrigation scheme. Our analysis suggests that irrigation reform successfully transferred authority and responsibility capacities to WUAs, including authorities for rule making, collective choice procedures, enforcement and sanctioning, and responsibilities to maintain and operate lateral canals and sub-drainage systems, ensure equity in decisions and water allocation, and resolve disputes among WUA members. We also found that the regulations (rules-in-form) granted WUAs the fiscal mandates and autonomy for self-sufficiency, but this goal is threatened by two issues. First, the WUAs struggle to raise revenue from members who are mostly low-income farmers experiencing low farm yields, low farmgate prices, and rising farm costs. Second, the WUAs continue to (over)rely on their government supervisory authority to mobilize revenue, risking the possibility of recentralizing fiscal control in the supervisory authority and not tackling the core issues impacting farmers’ fiscal well-being. We conclude by reflecting on the implications of our findings for understanding institutional designs in state-mandated decentralized irrigation reforms, particularly in sub-Saharan Africa.